Strategizing : new thinking about strategy, planning, and management - Bolland, Eric J. (Emerald Publishing Limited, 2020)
Strategy is an essential part of business, but strategizing often gets ignored or left behind. In this exciting new work, Eric J. Bolland introduces strategizing as a key component of strategy development and execution, showing strategizing as a way to aid organizations with their futures. To strategize successfully, businesses need a set of well-developed tools to help them perform specific actions continuously. Starting by tracing the origin and evolution of strategy and strategic planning, this exciting new guide puts forward advice on how to put strategy research into strategizing practice. In detailed chapters, Bolland addresses how strategizing works, with twenty real-world cases to show how theory can become reality, citing art, history, literature, science, psychology and philosophy to explore the human impulse to strategize. A valuable accompaniment for business students of strategy, as well as a practical handbook for staff and mid- and upper-level managers, this book is an essential read for anyone seeking guidance about planning the futures of their organizations.